2012
DOI: 10.1091/mbc.e11-08-0707
|View full text |Cite
|
Sign up to set email alerts
|

Axonal and dendritic synaptotagmin isoforms revealed by a pHluorin-syt functional screen

Abstract: Synaptotagmin-1 regulates synaptic vesicle fusion, but little is known about the remaining syt isoforms. Syt-pHluorin reporters are used to show that only two syts are on synaptic vesicles, whereas other isoforms are selectively targeted to dendrites, axons, or both axons and dendrites, where they undergo exocytosis and endocytosis with distinct kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 61 publications
(93 reference statements)
11
75
0
2
Order By: Relevance
“…Syt XI is the most abundant Syt isoform in astrocytes and is expressed more abundantly in the astrocytes as compared with the neurons; 27,28,30 however, its subcellular localization in astrocytes is not known. 41,42 Use of western blot analysis confirmed expression of Syt XI protein in primary astrocytes (Figure 4c). Using cell fractionation we found that endogenous Syt XI is enriched in the lysosome fractions (Figure 4d), demonstrating its localization on astrocyte lysosomes.…”
Section: Syt XI Regulates Lysosomal Exocytosis In Astrocytesmentioning
confidence: 75%
See 2 more Smart Citations
“…Syt XI is the most abundant Syt isoform in astrocytes and is expressed more abundantly in the astrocytes as compared with the neurons; 27,28,30 however, its subcellular localization in astrocytes is not known. 41,42 Use of western blot analysis confirmed expression of Syt XI protein in primary astrocytes (Figure 4c). Using cell fractionation we found that endogenous Syt XI is enriched in the lysosome fractions (Figure 4d), demonstrating its localization on astrocyte lysosomes.…”
Section: Syt XI Regulates Lysosomal Exocytosis In Astrocytesmentioning
confidence: 75%
“…28,[48][49][50] Similarly, Syt XI-containing vesicles undergo depolarization-triggered exocytosis in neurons. 42 Similar to neuronal lysosomes, 51 Syt XI-containing exocytic vesicles in neurons are acidic in nature and localize to dendrites. 42 To test whether, similar to Syt IV, the C2B domain of Syt XI helps trigger exocytosis, we mutated the three putative Ca 2+ -binding aspartate (D) residues in the C2B domain of Syt XI to asparagines (N) (SytXIrDN).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used live-cell imaging by total internal reflection fluorescence (TIRF) microscopy and complementary biochemical assays to determine whether sublytic MACs stimulate lysosome exocytosis in the RPE. We transfected primary RPE with Syt7 tagged with pHluorin, whose fluorescence is quenched in acidic lysosomal pH and relieved upon exposure to neutral pH after exocytosis (30). Individual exocytic events after addition of 10% NHS were detected as bright flashes of unquenched pHluorin in control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These include certain SNAREs (Kennedy et al, 2010;Lau et al, 2010;Suh et al, 2010), synaptotagmins (Dean et al, 2012), Rab-GTPases (Brown et al, 2005;Park et al, 2006), components of the exocyst complex (Gerges et al, 2006), and actin-based molecular motors (Wang et al, 2008). Acidification of vesicles is also an important determinant of their biogenesis and function (Weisz, 2003), yet the mechanisms controlling pH homeostasis of postsynaptic endosomes are not well understood.…”
Section: Introductionmentioning
confidence: 99%